How to sustain the Chinese economic miracle? The risk of unraveling the global rebalancing - Jörg Bibow (Levy Economics Institute of Bard College, 2010)
This paper investigates China's role in creating global imbalances, and the related call for a massive renminbi revaluation as a (supposed) panacea to forestall their reemergence as the world economy recovers from severe crisis. We reject the prominence widely attributed to China as a cause of global imbalances and the exclusive focus on the renminbi-dollar exchange rate as misguided. And we emphasize that China's response to the global crisis has been exemplary. Apart from acting as a growth leader in the global recovery by boosting domestic demand to offset the slump in exports, China has in the process successfully completed the first stage in rebalancing its economy, which is in stark contrast to other leading trading nations that have simply resumed previous policy patterns. The second stage in China's rebalancing will consist of further strengthening private consumption. We argue that this will be best supported by continued reliance on renminbi stability and capital account management, so as to assure that macroeconomic policies can be framed in line with domestic development requirements.
Keywords: E63; E65; F01; F42; 330; global imbalances; rebalancing; Renminbi revaluation; stimulus package; exportled growth